Comparative evaluation of the analgesic activity of several populations of Tunisian Citrullus colocynthis Schrad. immature fruits - Belsem MarzoukaÂ¥, Ehsen Halouib, Nadia Feninab, Mahjoub Aounia, Zohra Marzoukb (Journal of Applied Pharmaceutical Science, 2013)
Plant extracts are some of the most attractive sources of new drugs and have shown promising results for the treatment of pains, inflammations and immune-related diseases. Citrullus colocynthis Schrad., (cucurbitaceae) endemic in Tunisia, is widely used in folk medicine to treat many inflammation disorders. The aim of this study is to quantify the alkaloid level and to evaluate the acute toxicity of different populations of Citrullus colocynthis fruit aqueous extracts at immature state and then to screen their analgesic activities. After identification and acute toxicity essay, different populations of Citrullus colocynthis Schrad. aqueous fruit extracts were screened for analgesic activity using the acetic acid writhing test in mice. Yields of prepared extracts and alkaloid level are gravimetrically determined. Results show that alkaloid level vary upon the Citrullus colocynthis population. All extracts displayed analgesic activity at different doses without inducing acute toxicity. Topic results were obtained with immature fruits from south Tunisia. Experimental results have revealed that Citrullus colocynthis Schrad. is a potentially useful drug suitable for further evaluation, and its folk medicinal use, in all Tunisia, as an analgesic agent is validated for all tested Tunisian populations.
Keywords: Citrullus colocynthis Schrad, fruits, alkaloid, toxicity, analgesic.